Deployment of electric buses: Planning the fleet size and type, charging infrastructure and operations with an optimization-based model - Grilo T. C. (2022)
The current awareness about climate change creates the urgency in adjusting the services provided in public transport towards more sustainable operations. Recent studies have shown that the integration of electric vehicles into existing fleets is an alternative that allows reducing CO2 emissions, thus contributing to a more sustainable provision of services in the sector. When the aim is to achieve a full electrification of a bus fleet, several decisions need to be planned, such as i) the number of buses that are required, ii) the types of batteries used in those vehicles, iii) the charging technologies and strategies, iv) the location of the charging stations, and v) the frequency of charging. Nevertheless, although several planning studies have focused on the full electrification of a bus fleet, no study was found considering all these planning decisions that are deemed as essential for an adequate planning. Our study thus contributes to this gap in the literature, by proposing an optimization-based planning model that considers all these planning dimensions in the decision-making process related to the integration of electric buses in a public bus transport system – the MILP4ElectFleet model. All these decisions are evaluated while ensuring the minimization of in-vestment and operating costs. The MILP4ElectFleet model is applied to the Car-ris case study, a Portuguese public transport operator in the metropolitan area of Lisbon.